Right sided facial palsy more common in males while left sided facial palsy more common in females - Jain, Gaurav; Verma, Virendra (International Journal of Research in Medical Sciences, 2018)
Background: The study describes the retrospective analysis of 54 cases of facial nerve palsy patients seen in our neurophysiology Laboratory during February 2016 to January 2018. Methods: Clinically diagnosed cases of facial nerve palsy encountered at neurophysiology laboratory were analyzed on the basis of their diagnosis, age, sex, side affected and their seasonal occurrence. Patients were grouped in to four age groups of <20 yr, 21-40 yr, 41-60 yr and >60 yr. Results: Out of total 54 facial palsy cases with the mean age of 34.39±14.25 yr, 29 (53.70%) were males and 25 (46.30%) were females. Facial palsy was most common in 21-40 yr age group (42.59%, n=23), followed by 41-60 yr age group (29.63%, n=16). Nearly equal number of cases of right sided (26; 48.15%) and left sided (28; 51.85%) facial palsy were observe. However, right side facial palsy was more common in males with right side to left side facial palsy ratio of 1.90:1 and left sided facial palsy was more common in females with right side to left side facial palsy ratio of 1:2.57. Conclusions: Facial palsy cases are uniformly distributed among males and females with preponderance of right facial palsy in males and left facial palsy in females.